The Anti-Sartre? Michel Houellebecq and Politics. Issue 1 (April 2019) - Bowd, Gavin
Abstract : In his writings and other public interventions, Michel Houellebecq has never hidden his contempt for Jean-Paul Sartre and the pretentions of the intellectuel engagé . In his fiction and poetry there can be found a process of de-politicisation that accelerates across the generations, accompanied by an embrace of, or resignation to, the global market economy. However, politics has never been completely absent from Houellebecq's work, while he has not hesitated to make public interventions in the form of articles and interviews. This essay proposes to explore the relationship between Houellebecq and politics, in all its variety: communism, euroscepticism, conservatism; his "projet pour la France" set out in the Houellebecquian décor of Lui magazine, his reactions to recent terrorist attacks, his abstentionism during the 2017 Presidential elections, etc. What is the politics of Houellebecq? Is there/can there be a Houellebecquian engagement ?